Структура молекулярного димерного алкоксокомплексу хрому (ІІІ) з диметил-N-трихлороацетиламідофосфатом - Труш, Є.А.; Труш, В.А.; Домасевич, К.В.; Амірханов, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
A new coordination compound of chromium (III) with dimethyl-N-trichloroacetylamidophosphate (L¯ = Cl3CC(O)NP(O)(OCH3)2) has been obtained. Based on IR data, the bidentate coordination mode of the carbacylamidophosphate ligand is suggested. The centrosymmetric bi-nuclear complex [Cr2(L)4(μ2−OCH3)2] has molecular structure according to X-ray analysis. The phosphoramidic ligands are coordinated in a bidentate manner via oxygen atoms of phosphoryl and carbonyl groups, and the coordination polyhedra represent the cis-isomer. The coordination environment of the central ion possesses a distorted octahedral geometry with c.n. = 6. The polyhedron (CrO6) comprises 4O from two bidentate phosphorylic ligands and 2O from bridging methoxide ions.